Electric and electronic measurment and testing - William Bolton (1933- (Longman, 1992)
The book provides the concepts of measurement and testing, including the sources of errors, reliability and standars; the terms used in performance specifications; the principles of data processing and display; the principles and characteristics of basic and specialist test equipment - analogue meters, digital maters, recorders, bridges, wattmeters, oscilloscopes, counters, signal sources, digital circuit test instruments and automatic instruments; the principles of measurement systems - transducers, signal conditioning and processing and data transmission; the principles of test procedures for manual and automatic testing